Detection and typing of common human papillomaviruses among Jordanian patients - Al Bdour, Suzan; Akkash, Laith; Shehabi, Asem A. (Journal of medical virology, 2013)
The epidemiology of human papillomaviruses (HPVs) genotype distribution of cutaneous warts in Jordanian patients were studied. A total of 200 samples were collected using skin swabs from patients with warts attending the dermatology clinic at the Jordan University Hospital over the period of June 2010 to October 2010. Another 100 control samples were taken from healthy Jordanian individuals with no current or previous history of warts. DNA extraction and sequencing was carried out using PCR with the FAP primer pair to detect HPV DNA, followed by multiple‐type‐specific (Multiplex) PCR combined with DNA sequencing. The prevalence of HPV among Jordanian patients tested with warts diagnosed clinically was 82% (157/192); of these 45% (87/192) were detected by FAP PCR method, and 37% (70/192) were detected by multiplex PCR method. Sequencing of the FAP positive samples shows that HPV 2 was associated with the highest prevalence (36%), followed by HPV 27 (28%) and HPV 57 (21%). A total of 6% of healthy persons were positive for HPV DNA. In conclusion, this study demonstrates that alpha HPV types (HPV 2, HPV 27, and HPV 57) are associated with the most prevalent cutaneous warts in Jordanian patients J. Med. Virol. 85: 1058–1062, 2013. © 2013 Wiley Periodicals, Inc.